Online Learning in the Time of Crisis: A Study of EFL Students’ Attitudes - Mustafa Fuzi Elshawish; Jalal Ali Belshaikh (Journal of English as A Foreign Language Teaching and Research, 2021)
Abstract This article discussed the importance of utilizing online learning during times of crises with special emphasis on the situation in Libya. In spite of the dangerous current situation i.e., the wide spread of a deadly Corona Virus, educational institutions (schools, universities, and academies) in Libya are still based on traditional procedures of learning, i.e., they adopt the traditional way of face-to-face classes and meetings. Although there have been some attempts of using blended learning, still most of the institutions are stuck with old methods. The current situation in the country since the beginning of the unrest in 2011 and recently with the emergence of a sudden outbreak of a deadly disease called Covid-19 caused by a Corona Virus shook the entire country and called for an urgent intervention. However, because of the fragile situation and the decrepit infrastructure in Libya, challenges to the education system are huge. This article highlighted the perceptions of a group of postgraduate students of English on online learning and also included the Advantages, Disadvantages, Opportunities, and Barriers (ADOB) analysis of e-learning modes in the time of crisis. The findings revealed that access to online learning in Libya was hindered by many challenges, and consequently students perceived online learning as inefficient. The paper also provided some suggestions for academic institutions of how to deal with challenges associated with online learning.